Leaf development in some ferns with variable dissection patterns (Dryopteridaceae and Lomariopsidaceae) - Cruz, Rafael; Prado, Jefferson [UNESP]; Albuquerque Melo-de-Pinna, Gladys Flavia de (Elsevier B.V., 2020)
Although ferns are an important group for understanding leaf evolution, their developmental processes are still few understood. To better understand the organization of meristems and ontogeny of leaves in ferns, we studied their development in Elaphoglossum vagans (Mett.) Hieron., Lastreopsis amplissima (C. Presl) Tindale, Lomariopsis marginata (Schrad.) Kuhn, Mickelia scandens (Aubl.) R.C. Moran et al., Polybotrya cylindrica Kaulf., and Rumohra adiantiformis (G. Forst.) Ching, by using anatomical techniques. In addition, we observed herbarium specimens of those species, plus Elaphoglossum lingua (C. Presl) Brack, searching for unusual morphologies that may occur, that could represent a deviation from developmental processes here described. We propose hypotheses to explain these natural mutants based on known mechanisms of development. Shoot apical meristems of these species bear the typical tetrahedral cell with three dividing faces and the leaf apical meristem has two dividing faces. The leaf forms marginal meristems with enlarged initial cells, each of them bearing similarities to the leaf apical cell geometry and size, except in the simple-leaved fern Elaphoglossum vagans. Pinnae and segments primordia have grouped apical cells that are contiguous with their own marginal cells. In multi-pinnate leaves, one of these grouped apical cells in pinnae may enlarge and become similar to the leaf apical cell, indicating a reiterative process. The observed plants with unusual morphologies include plants with mixed reproductive identity, differential marginal growth, compromised apical growth, and reduced determinacy, supporting previous studies for leptosporangiate ferns. Apical and marginal cells of ferns may be homologous between them. Their characteristic geometry may allow specific cell divisions and their interconvertibility may drive the balance between apical and marginal growth. Unusual activity of these cells or changes in transcription factors may generate the observed abnormalities. A reiterative development in fern leaves supports the homology with shoots and the identity-in-parallel of their divisions.
Keywords: Determinacy; Ferns; Leaf development; Meristems; Pinnae; Reiteration; Segments